Hot-melt adhesive composition, precoated surface material for automobile interior, automobile interior material, and method for producing bonded object
Patent Information
- Application Number
- JP2022104621
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-06-29
AI Technical Summary
Conventional hot melt adhesives require time to solidify, making it difficult to peel them from molds, leading to poor workability and manual peeling issues, especially when using methods like vacuum forming.
A hot melt adhesive composition comprising crystalline polyolefin, amorphous polyolefin, and polypropylene wax, with specific ratios and properties, allowing for easy mold release and improved adhesion to polyolefin substrates.
The composition provides excellent adhesion to polyolefin substrates with good mold releasability, enhancing workability and reducing manual peeling requirements.
Smart Images

Figure 2024004788000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a hot melt adhesive composition, a precoated surface material for automobile interiors using the same, and an automobile interior material. [Background technology]
[0002] Hot melt adhesives are solid at room temperature, and are applied to substrates after being heated and melted, and then bond the substrates together by cooling and solidifying. Compared to solvent-based adhesives, hot melt adhesives have the advantage of reducing VOCs and improving productivity by eliminating the need for a drying process, and are used in a variety of applications, such as automobile manufacturing.
[0003] Patent Document 1 discloses a hot melt adhesive composition containing a hydrocarbon cyclic polymer, an α-olefin polymer, and a tackifier resin.
[0004] Patent Document 2 discloses a hot melt adhesive composition containing an α-olefin copolymer polymerized using a multi-site catalyst, an α-olefin copolymer polymerized using a single-site catalyst, an ethylene-polar group-containing monomer copolymer, a hydrogenated tackifier resin, and a polypropylene wax in a specific ratio. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] WO2018 / 012593 [Patent Document 2] WO2018 / 100672 Summary of the Invention [Problem to be solved by the invention]
[0006] When using a hot melt adhesive, depending on the type of bonding method, a process of peeling the hot melt adhesive from the mold is required (for example, vacuum molding). Patent Document 1 and Patent Document 2 do not discuss the process of peeling the hot melt adhesive from the mold. Conventional hot melt adhesives take time to solidify from a molten state, and during that time the hot melt adhesive cannot be easily peeled off from the mold, which can lead to poor workability. In addition, when a conventional hot melt adhesive is used, the hot melt adhesive remains after peeling from the mold, which can pose a problem from the viewpoint of workability, as it requires manual peeling and cleaning.
[0007] Therefore, an object of the present disclosure is to provide a hot melt adhesive that has good adhesion to resin substrates, particularly polyolefin substrates such as polypropylene, and also has workability (mold releasability) that allows the adhesive to be easily peeled off from a mold. [Means for solving the problem]
[0008] That is, the present disclosure includes the following: [Section 1] A crystalline polyolefin (A) having a Shore A hardness of 80 or more; Amorphous polyolefin (B) and Polypropylene wax (C) Including, A hot melt adhesive composition, wherein the amount of the polypropylene wax (C) is 60 parts by weight or more and 300 parts by weight or less per 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). [Section 2] Item 2. The hot melt adhesive composition according to item 1, wherein the melting point of the crystalline polyolefin (A) is 80° C. or higher. [Section 3] Item 3. The hot melt adhesive composition according to item 1 or 2, wherein the crystalline polyolefin (A) comprises an ethylene-propylene copolymer. [Section 4] 4. The hot melt adhesive composition according to any one of items 1 to 3, wherein the amorphous polyolefin (B) has a softening point of 100° C. or higher. [Section 5] Item 5. The hot melt adhesive composition according to any one of items 1 to 4, wherein the amorphous polyolefin (B) comprises at least one selected from the group consisting of an ethylene-propylene binary copolymer and an ethylene-propylene-butene ternary copolymer. [Section 6] 6. The hot melt adhesive composition according to any one of items 1 to 5, wherein the polypropylene wax (C) has a softening point of 130° C. or higher. [Section 7] Item 7. The hot melt adhesive composition according to any one of items 1 to 6, further comprising a tackifier (D). [Section 8] Item 8. The hot melt adhesive composition according to item 7, wherein the softening point of the tackifier (D) is 90° C. or higher. [Section 9] Item 8. The hot melt adhesive composition according to item 7, wherein the tackifier (D) comprises at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins, and terpene phenol resins. [Section 10] 10. The hot melt adhesive composition according to any one of items 1 to 9, further comprising an antioxidant (E). [Section 11] 11. The hot melt adhesive composition according to any one of items 1 to 10, further comprising an inorganic filler (F). [Section 12] Item 12. The hot melt adhesive composition according to any one of items 1 to 11, comprising an elastomer (G). [Section 13] Item 13. The hot melt adhesive composition according to any one of items 1 to 12, having a melt viscosity at 180°C of 15,000 mPa·s or more and 100,000 mPa·s or less. [Section 14] Item 14. The hot melt adhesive composition according to any one of items 1 to 13, which is for use in automobile interior materials. [Section 15] Item 15. A precoated skin material for automobile interiors, comprising: a skin material for automobile interiors; and a hot melt adhesive layer formed from the hot melt adhesive composition according to any one of items 1 to 14 on a back surface of the skin material for automobile interiors. [Section 16] Item 16. An automobile interior material comprising: an automobile interior molded article; and the precoated skin material for automobile interiors according to item 15, which is adhered to the automobile molded article via the hot melt adhesive layer. [Section 17] A method for producing an adhesive body, comprising the steps of: The adhesive body has a first substrate and a second substrate adhered to the first substrate via a hot melt adhesive layer formed from the hot melt adhesive composition according to any one of items 1 to 14, A method for producing an adhesive article, comprising a step of contacting a mold with the hot melt adhesive composition. Effect of the Invention
[0009] The hot melt adhesive of the present disclosure has good adhesion, particularly to polyolefin substrates such as polypropylene, and also has good mold releasability and excellent workability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Hot melt adhesive composition> The hot melt adhesive composition of the present disclosure contains a crystalline polyolefin (A), an amorphous polyolefin (B), and a polypropylene wax (C). In addition to (A) to (C), the hot melt adhesive composition of the present disclosure may further contain, as necessary, one or more selected from a tackifier (D), an antioxidant (E), an inorganic filler (F), an elastomer (G), a plasticizer (H), and other additives.
[0011] [(A) Crystalline polyolefin] The hot melt adhesive composition of the present disclosure includes a crystalline polyolefin (A). The crystalline polyolefin (A) is a polyolefin having high crystallinity. The crystalline polyolefin (A) is distinguished from other components described in the present specification in terms of crystallinity, Shore A hardness, and / or molecular weight, etc. Typically, the crystallinity of the crystalline polyolefin (A) is 20% or more. Typically, the Shore A hardness of the crystalline polyolefin (A) is 80 or more. Typically, the weight average molecular weight of the crystalline polyolefin (A) is 40,000 or more.
[0012] The crystallinity of the crystalline polyolefin (A) may be 20% or more, 25% or more, 30% or more, or 35% or more. The crystallinity of the crystalline polyolefin (A) may be 100% or less, 98% or less, 95% or less, 90% or less, or 85% or less. It is preferable that the crystallinity is equal to or greater than the lower limit in order to better achieve the effects of the present disclosure. The crystallinity can be measured, for example, by differential scanning calorimetry, X-ray diffraction of a polymer, or the like. In the present disclosure, "crystalline" may mean a property in which a clear endothermic peak derived from a crystalline portion is observed in differential scanning calorimetry, while "amorphous" may mean a property in which a clear endothermic peak derived from a crystalline portion is not observed in differential scanning calorimetry.
[0013] The Shore A hardness of the crystalline polyolefin (A) may be 80 or more, 85 or more, 90 or more, or 95 or more, preferably 85 or more, more preferably 90 or more. The Shore A hardness of the crystalline polyolefin (A) may be 100 or less, 99 or less, 98 or less, or 97 or less. The Shore A hardness can be used as an index of the cohesive force of a resin, and can be one of the indexes of adhesiveness at room temperature and in hot conditions. It is preferable that the Shore A hardness is within the above range in terms of better achieving the effects of the present disclosure.
[0014] The melting point of the crystalline polyolefin (A) may be 60° C. or more, 70° C. or more, 80° C. or more, 90° C. or more, 100° C. or more, or 110° C. or more, and is preferably 80° C. or more. The melting point of the crystalline polyolefin (A) may be 150° C. or less, 140° C. or less, 130° C. or less, 120° C. or less, 110° C. or less, 100° C. or less, or 90° C. or less, and is preferably 120° C. or less, for example, 110° C. or less, or 100° C. or less. It is preferable that the melting point is within the above range in terms of better exerting the effects of the present disclosure.
[0015] The glass transition temperature of the crystalline polyolefin (A) may be -150°C or higher, -125°C or higher, -100°C or higher, -75°C or higher, -50°C or higher, or -25°C or higher. The glass transition temperature of the crystalline polyolefin (A) may be 20°C or lower, 10°C or lower, 0°C or lower, -10°C or lower, or -20°C or lower, preferably 0°C or lower, more preferably -10°C or lower. It is preferable that the glass transition temperature is the above upper limit or lower from the viewpoint of low-temperature adhesion.
[0016] The crystalline polyolefin (A) is typically thermoplastic. The MFR of the crystalline polyolefin (A) may be 3g / 10min or more, 5g / 10min or more, 7g / 10min or more, 10g / 10min or more, 12g / 10min or more, or 15g / 10min or more, preferably 5g / 10min or more, more preferably 7g / 10min or more. The MFR of the crystalline polyolefin (A) may be 40g / 10min or less, 30g / 10min or less, 20g / 10min or less, 15g / 10min or less, or 10g / 10min or less. It is preferable that the MFR is in the range of the above lower limit or more from the viewpoint of low melt viscosity and coating stability. The MFR can be measured based on JIS K7210.
[0017] The weight average molecular weight of the crystalline polyolefin (A) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, and is preferably 100,000 or more. The weight average molecular weight of the crystalline polyolefin (A) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, and is preferably 1,000,000 or less, for example, 600,000 or less. It is preferable that the weight average molecular weight is in the above range from the viewpoint of better exerting the effects of the present disclosure.
[0018] The crystalline polyolefin (A) is a polymer having a repeating unit derived from an olefin. The crystalline polyolefin (A) is preferably an α-olefin-based polymer having a repeating unit derived from an α-olefin, particularly an α-olefin-based copolymer. The crystalline polyolefin (A) may be a homopolymer, a copolymer, or a mixture thereof. The form of the copolymer may be any of random copolymerization, block copolymerization, graft copolymerization, etc.
[0019] Examples of repeating units contained in the crystalline polyolefin (A) include repeating units derived from ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these may be contained alone or in combination of two or more.
[0020] The crystalline polyolefin (A) preferably contains a repeating unit derived from propylene among the repeating units described above, and may contain both a repeating unit derived from propylene and a repeating unit derived from another α-olefin (e.g., ethylene). Of the repeating units constituting the crystalline polyolefin (A), the repeating units derived from propylene may be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.
[0021] Specific examples of the crystalline polyolefin (A) include copolymers of olefins such as ethylene homopolymer, propylene homopolymer, ethylene-propylene copolymer, propylene-1-butene copolymer, ethylene-1-butene copolymer, ethylene-1-octene copolymer, ethylene-1-hexene copolymer, and ethylene-propylene-1-butene copolymer, and a preferred example is an ethylene-propylene copolymer. These may be used alone or in combination of two or more kinds.
[0022] Representative examples of commercially available crystalline polyolefins (A) include the Tafmer series, such as trade names "Tafmer XM-7090", "Tafmer XM-7080", "Tafmer XM-7070", "Tafmer XM-5090", "Tafmer XM-5080", "Tafmer XM-5070", "Tafmer BL-2491M", and "Tafmer DF110" manufactured by Mitsui Chemicals; the VERSIFY series, such as trade names "VERSIFY3000" and "VERSIFY4200" manufactured by Dow Chemical; the Vistamaxx series, such as trade names "Vistamaxx8880", "Vistamaxx3000", and "Vistamaxx3980FL" manufactured by ExxonMobil; and "L-MODU S901", "L-MODU S600", and "L-MODU S400" manufactured by Idemitsu Kosan Co., Ltd. The crystalline polyolefins (A) may be used alone or in combination of two or more kinds.
[0023] [(B) Amorphous polyolefin] The hot melt adhesive composition of the present disclosure includes an amorphous polyolefin (B). The amorphous polyolefin (B) is a polyolefin that has no crystallinity or has a small amount of crystallinity, and can impart flexibility. The amorphous polyolefin (B) is distinguished from other components described in this specification in terms of crystallinity and / or molecular weight. Typically, the crystallinity of the amorphous polyolefin (B) is less than 20%. Typically, the amorphous polyolefin (B) has a weight average molecular weight of 40,000 or more.
[0024] The degree of crystallinity of the amorphous polyolefin (B) may be 0% or more, 3% or more, or 5% or more. The degree of crystallinity of the amorphous polyolefin (B) may be less than 20%, 15% or less, 10% or less, 5% or less, 3% or less, or 1% or less. It is preferable that the degree of crystallinity is equal to or less than the upper limit value in order to more effectively achieve the effects of the present disclosure. The degree of crystallinity can be measured, for example, by differential scanning calorimetry, X-ray diffraction of a polymer, or the like.
[0025] The softening point of the amorphous polyolefin (B) may be 70°C or more, 80°C or more, 90°C or more, 100°C or more, 110°C or more, 120°C or more, or 130°C or more, preferably 80°C or more, for example 100°C or more. The softening point of the amorphous polyolefin (B) may be 180°C or less, 170°C or less, 160°C or less, 150°C or less, 140°C or less, 130°C or less, 120°C or less, or 110°C or less, preferably 160°C or less, for example 140°C or less. It is preferable that the softening point is within the above range in terms of better exerting the effects of the present disclosure. The softening point can be measured by the ring and ball method.
[0026] The glass transition temperature of the amorphous polyolefin (B) may be −150° C. or higher, −125° C. or higher, −100° C. or higher, −75° C. or higher, −50° C. or higher, or −25° C. or higher. The glass transition temperature of the crystalline polyolefin (A) may be 20° C. or lower, 10° C. or lower, 0° C. or lower, −10° C. or lower, or −20° C. or lower, preferably 0° C. or lower, more preferably −10° C. or lower. It is also preferable that the glass transition temperature is the above upper limit or lower from the viewpoint of low-temperature adhesiveness.
[0027] The amorphous polyolefin (B) is typically thermoplastic. The MFR of the amorphous polyolefin (B) may be 3g / 10min or more, 5g / 10min or more, 7g / 10min or more, 10g / 10min or more, 12g / 10min or more, or 15g / 10min or more, preferably 5g / 10min or more, more preferably 7g / 10min or more. The MFR of the amorphous polyolefin (B) may be 40g / 10min or less, 30g / 10min or less, 20g / 10min or less, 15g / 10min or less, or 10g / 10min or less. It is preferable that the MFR is in the range of the above lower limit or more from the viewpoint of low melt viscosity and coating stability. The MFR can be measured based on JIS K7210.
[0028] The weight average molecular weight of the amorphous polyolefin (B) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, and is preferably 100,000 or more. The amorphous polyolefin (B) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, and is preferably 1,000,000 or less, for example, 600,000 or less. It is preferable that the weight average molecular weight is in the above range from the viewpoint of better exerting the effects of the present disclosure.
[0029] The amorphous polyolefin (B) is a polymer having a repeating unit derived from an olefin. The amorphous polyolefin (B) is preferably an α-olefin-based polymer having a repeating unit derived from an α-olefin, particularly an α-olefin-based copolymer. The amorphous polyolefin (B) may be a homopolymer, a copolymer, or a mixture thereof. The form of the copolymer may be any of random copolymerization, block copolymerization, graft copolymerization, etc.
[0030] Examples of repeating units contained in the amorphous polyolefin (B) include repeating units derived from, for example, ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these may be contained alone or in combination of two or more kinds.
[0031] The amorphous polyolefin (B) preferably contains a repeating unit derived from propylene among the repeating units described above, and may contain both a repeating unit derived from propylene and a repeating unit derived from another α-olefin (e.g., ethylene). Of the repeating units constituting the amorphous polyolefin (B), the repeating units derived from propylene may be 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, or 70 mol% or more, and preferably 30 mol% or more.
[0032] Specific examples of the amorphous polyolefin (B) include copolymers of olefins such as ethylene homopolymers, propylene homopolymers, ethylene-propylene copolymers, propylene-1-butene copolymers, ethylene-1-butene copolymers, ethylene-1-octene copolymers, ethylene-1-hexene copolymers, and ethylene-propylene-1-butene copolymers, and preferred examples include ethylene-propylene binary copolymers and / or ethylene-propylene-butene ternary copolymers. These may be used alone or in combination of two or more.
[0033] Representative examples of commercially available amorphous polyolefins (B) include the VESTOPLAST series, such as trade names "VESTOPLAST 308", "VESTOPLAST 508", "VESTOPLAST 520", "VESTOPLAST 608", "VESTOPLAST EP V2103", "VESTOPLAST EP V2094", "VESTOPLAST 708", "VESTOPLAST 750", "VESTOPLAST 751", "VESTOPLAST 792", "VESTOPLAST 828", "VESTOPLAST 888", "VESTOPLAST 891", and "VESTOPLAST EP 807", manufactured by Evonik; and the RT series, such as trade names "RT2280", "RT2385", "RT2585", and "RT2780", manufactured by REXtac.
[0034] [(C) Polypropylene wax] The hot melt adhesive composition of the present disclosure contains a polypropylene-based wax (C). The polypropylene-based wax (C) is a wax having a repeating unit derived from propylene. The polypropylene-based wax (C) generally has a low molecular weight (less than 40,000), and can impart coatability and wettability to an adherend by lowering the viscosity of the hot melt adhesive. In addition, the polypropylene-based wax (C) can promote the crystallization and solidification of the crystalline polyolefin (A), improve the solidification speed of the hot melt adhesive, and improve the mold releasability.
[0035] The softening point of the polypropylene wax (C) is 90°C or higher, 100°C or higher, 110°C or higher, 120°C or higher, 130°C or higher, 140°C or higher, or 150°C or higher, preferably 110°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher. The softening point of the polypropylene wax (C) may be 220°C or lower, 210°C or lower, 190°C or lower, 180°C or lower, 170°C or lower, 160°C or lower, or 150°C or lower, and is preferably 190°C or lower, for example, 160°C or lower. It is preferable that the softening point is within the above range from the viewpoint of better achieving the effects of the present disclosure. The softening point can be measured by the ring and ball method. It is also preferable that the softening point of the polypropylene wax (C) is below the above upper limit from the viewpoint of setting the melting temperature low and shortening the working time.
[0036] The weight average molecular weight of the polypropylene wax (C) may be 3,000 or more, 5,000 or more, or 7,000 or more, and is preferably 3,000 or more. The weight average molecular weight of the polypropylene wax (C) may be less than 40,000, 35,000 or less, 30,000 or less, 20,000 or less, or 10,000 or less, and is preferably 20,000 or less. It is preferable that the weight average molecular weight is in the above range from the viewpoint of better exerting the effects of the present disclosure.
[0037] The polypropylene wax (C) may have a repeating unit other than the repeating unit derived from propylene, for example, a repeating unit derived from an α-olefin. The polypropylene wax (C) may be a low molecular weight polyolefin, particularly a low molecular weight α-olefin polymer. The polypropylene wax (C) may be a homopolymer, a copolymer, or a mixture thereof. The copolymer may be in the form of any of random copolymerization, block copolymerization, graft copolymerization, etc.
[0038] Examples of repeating units contained in the polypropylene wax (C) other than the repeating units derived from propylene include repeating units derived from ethylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, and these may be contained alone or in combination of two or more.
[0039] Of the repeating units constituting the polypropylene-based wax (C), the repeating units derived from propylene may be 20 mol % or more, 30 mol % or more, 40 mol % or more, 50 mol % or more, 60 mol % or more, or 70 mol % or more, and is preferably 30 mol % or more.
[0040] Representative examples of commercially available polypropylene wax (C) include the Viscol series, such as "Viscol 660-P", "Viscol 550-P", "Viscol 440-P", and "Viscol 330-P" manufactured by Sanyo Chemical Industries; the Hiwax series, such as "Hiwax 100P", "Hiwax 200P", "Hiwax 400P", "Hiwax 800P", "Hiwax 410P", and "Hiwax 420P" manufactured by Mitsui Chemicals; and the Ricosene series, such as "Ricosene PP6102", "Ricosene PP6502", and "Ricosene PP7502" manufactured by Client Chemicals. The polypropylene wax (C) may be used alone or in combination of two or more kinds. Furthermore, waxes other than the polypropylene wax (C) may be blended within a range that does not impair the desired physical properties.
[0041] [(D) Tackifier] The hot melt adhesive composition of the present disclosure may include a tackifier (D). The tackifier (D) may improve tackiness when melted.
[0042] The softening point of the tackifier (D) is 90°C or more, 100°C or more, 110°C or more, 120°C or more, 130°C or more, 140°C or more, or 150°C or more, preferably 110°C or more, more preferably 120°C or more, and even more preferably 130°C or more. The softening point of the tackifier (D) may be 220°C or less, 210°C or less, 190°C or less, 180°C or less, 170°C or less, 160°C or less, or 150°C or less, and is preferably 190°C or less, for example 160°C or less. It is preferable that the softening point is in the above range from the viewpoint of better achieving the effects of the present disclosure. The softening point can be measured by the ring and ball method. It is also preferable that the softening point of the tackifier (D) is below the above upper limit from the viewpoint of setting the melting temperature low and shortening the working time.
[0043] Examples of the tackifier (D) include rosin resin, rosin ester, disproportionated rosin ester, hydrogenated rosin ester, polymerized rosin, aliphatic hydrocarbon resin, aliphatic aromatic copolymer resin, aromatic petroleum resin, hydrogenated petroleum resin, terpene resin, hydrogenated terpene resin, modified terpene resin, hydrogenated modified terpene resin, terpene phenol resin, hydrogenated terpene phenol resin, styrene resin, coumarone resin, indene resin, etc. Among them, from the viewpoint of compatibility with polyolefin, preferred examples include hydrogenated petroleum resin, terpene resin, and terpene phenol resin. Note that the tackifier (D) is distinguished from other components such as polyolefin from the viewpoint of the presence or absence of intramolecular double bonds, intramolecular polar groups, intramolecular hydrocarbon groups, etc.
[0044] Representative examples of commercially available tackifiers (D) include the Arcon series, such as trade names "Arcon P-90", "Arcon P-100", "Arcon P-115", "Arcon P-140", "Arcon M-90", "Arcon M-100", "Arcon M-115", and "Arcon M-135" manufactured by Arakawa Chemical Industries, Ltd.; the "Imarv" series, such as trade names "Imarv S-100", "Imarv S-110", "Imarv P-100", "Imarv P-125", and "Imarv P-140" manufactured by Idemitsu Kosan Co., Ltd.; and the "T-REZ HA125", "T-REZ HB125", and "T-REZ Examples of the tackifier include the T-REZ series, such as "OP501" and the like, and the YS resin series or YS polystar series, such as "YS resin PX1250", "YS resin PX1150", "YS resin PX1000", "YS resin PX1150N", "YS resin TO125", "YS resin TO115", "YS resin TO105", "YS polystar T160", "YS polystar T145", "YS polystar T130", "YS polystar T115", "YS polystar T100", and "YS polystar UH115" manufactured by Yasuhara Chemical Co., Ltd.; and the FTR series, such as "FTR6100", "FTR6110", and "FTR6125" manufactured by Mitsui Chemicals, Inc. The tackifier (D) may be used alone or in combination of two or more kinds. Furthermore, a tackifier having a softening point of less than 90 ° C. may be blended within a range that does not impair the desired physical properties.
[0045] [(E) Antioxidants] The hot melt adhesive composition of the present disclosure may contain an antioxidant (E). By containing the antioxidant (E), the thermal stability is improved, which may be preferable from the viewpoint of favorably exhibiting the effects of the present disclosure.
[0046] Examples of the antioxidant (E) include hindered phenols, polyphenols, bisphenols, phosphates, thioethers, hydrosulphites, benzimidazoles, and aromatic secondary amines.
[0047] Representative examples of commercially available antioxidants (E) include the Irganox series, such as trade names "Irganox 1010", "Irganox 1035", "Irganox 1076", "Irganox 1098", "Irganox 1330", "Irganox 245", "Irganox 259", "Irganox 3114", "Irganox 565", and "Irgaphos 168" manufactured by BASF; and the "ADK STAB" series, such as trade names "ADK STAB AO-20", "ADK STAB AO-30", "ADK STAB AO-40", "ADK STAB AO-50", "ADK STAB AO-60", "ADK STAB AO-80", "ADK STAB AO-330", "ADK STAB PEP-8", "ADK STAB PEP-36", "ADK STAB HP-10", "ADK STAB 2112", and "ADK STAB AO-412S" manufactured by ADEKA. The antioxidant (E) may be used alone or in combination of two or more kinds.
[0048] [(F) Inorganic filler] The hot melt adhesive composition of the present disclosure may contain an inorganic filler (F). By adding the inorganic filler (F), it is possible to adjust the adhesiveness, dripping property, specific gravity, and the like.
[0049] Examples of the inorganic filler (F) include calcium carbonate (heavy calcium carbonate, surface-untreated calcium carbonate, surface-treated calcium carbonate (e.g., fatty acid-treated calcium carbonate, etc.), needle-shaped crystalline calcium carbonate), silica (fume silica, hydrophobic silica, precipitated silica, etc.), talc, mica, clay, chrysotile, wollastonite, carbon black, graphite, balloons (shirasu balloons, glass balloons, silica balloons, etc.), inorganic fibers (glass fibers, metal fibers, etc.), titanium oxide, aluminum oxide, aluminum borate, silicon carbide, silicon nitride, potassium titanate, magnesium borate, titanium diboride, aluminum flakes, aluminum powder, iron powder, etc. The inorganic filler (F) may be used alone or in combination of two or more kinds.
[0050] [(G) Elastomer] The hot melt adhesive composition of the present disclosure may include an elastomer (G). The elastomer (G) is a polymer that exhibits elasticity. The elastomer (G) may be thermosetting or thermoplastic, and is preferably thermoplastic. The elastomer (G) is distinguished from the other components described herein in terms of crystallinity, Shore A hardness, and / or molecular weight. Typically, the elastomer (G) is not amorphous. Typically, the elastomer (G) has a Shore A hardness of less than 80. Typically, the elastomer (G) has a weight average molecular weight of 40,000 or more.
[0051] The Shore A hardness of the elastomer (G) may be 20 or more, 30 or more, 40 or more, 50 or more, 60 or more, or 70 or more, and is preferably 40 or more. The Shore A hardness of the elastomer (G) may be less than 80, 75 or less, 70 or less, 65 or less, or 60 or less. It is preferable that the Shore A hardness of the elastomer (G) is within the above range from the viewpoint of better exerting the effects of the present disclosure.
[0052] The MFR of the elastomer (G) may be 3g / 10min or more, 5g / 10min or more, 7g / 10min or more, 10g / 10min or more, 12g / 10min or more, or 15g / 10min or more, preferably 5g / 10min or more, more preferably 7g / 10min or more. The MFR of the elastomer (G) may be 40g / 10min or less, 30g / 10min or less, 20g / 10min or less, 15g / 10min or less, or 10g / 10min or less. It is preferable that the MFR is in the range of the above lower limit or more from the viewpoint of low melt viscosity and coating stability. The MFR can be measured based on JIS K7210.
[0053] The weight average molecular weight of the elastomer (G) may be 40,000 or more, 50,000 or more, 75,000 or more, 100,000 or more, 200,000 or more, 300,000 or more, or 500,000 or more, and is preferably 100,000 or more. The weight average molecular weight of the elastomer (G) may be 5,000,000 or less, 2,000,000 or less, 1,500,000 or less, 1,200,000 or less, 1,000,000 or less, 800,000 or less, 600,000 or less, 400,000 or less, or 200,000 or less, and is preferably 1,000,000 or less, for example, 600,000 or less. It is preferable that the weight average molecular weight is in the above range from the viewpoint of better exerting the effects of the present disclosure.
[0054] Examples of the elastomer (G) include rubber-based elastomers, olefin-based elastomers, styrene-based elastomers (e.g., hydrogenated or non-hydrogenated styrene-based elastomers), vinyl chloride-based elastomers, urethane-based elastomers, ester-based elastomers, and amide-based elastomers. From the viewpoint of compatibility, olefin-based elastomers are preferred. The olefin-based elastomer may be an olefin-based elastomer having a repeating unit derived from propylene.
[0055] Representative examples of commercially available elastomers (G) include the Tafmer PN series, such as trade names "Tafmer PN-2070" and "Tafmer PN-3560" manufactured by Mitsui Chemicals, Inc.; the INFUSE series, such as trade names "INFUSE9807", "INFUSE9817", and "INFUSE9990" manufactured by Dow Chemical Company; and the Vistamaxx series, such as trade names "Vistamaxx6502" and "Vistamaxx6202" manufactured by ExxonMobil Corporation. The elastomers (G) may be used alone or in combination of two or more kinds.
[0056] [(H) Plasticizer] The hot melt adhesive composition of the present disclosure may contain a plasticizer (H). The plasticizer (H) is an oily substance such as a low molecular weight compound containing a chain alkyl group or an olefin oligomer. The plasticizer (H) can improve the coatability and wettability to the adherend by lowering the viscosity of the hot melt adhesive.
[0057] The weight average molecular weight of the plasticizer (H) may be 100 or more, 300 or more, or 500 or more. The weight average molecular weight of the plasticizer (H) may be less than 3000, 2500 or less, 20000 or less, 1500 or less, or 1000 or less, and is preferably 2000 or less. It is preferable that the weight average molecular weight is within the above range from the viewpoint of better exerting the effects of the present disclosure.
[0058] Examples of the plasticizer (H) include liquid paraffin, process oil, phthalic acid plasticizer, butene oligomer, butadiene oligomer, liquid ethylene-propylene oligomer, liquid rubber, etc., and from the viewpoint of compatibility, butene oligomer or liquid ethylene-propylene oligomer is preferred.
[0059] Representative examples of commercially available plasticizers (H) include polybutene series such as "NOF Polybutene 0N", "NOF Polybutene 015N", "NOF Polybutene 3N", "NOF Polybutene 10N", "NOF Polybutene 30N", and "NOF Polybutene 200N" manufactured by NOF Corporation; and Lucant series such as "LUCANT LX004", "LUCANT LX010", "LUCANT LX020", "LUCANT LX100", "LUCANT LX200", "LUCANT LX400", and "LUCANT LX900Z" manufactured by Mitsui Chemicals, Inc. The plasticizers (H) may be used alone or in combination of two or more kinds.
[0060] [(I) Other ingredients] In addition to the above, the hot melt adhesive composition of the present disclosure may contain other components (I) as necessary. Examples of other components (I) include colorants (e.g., red iron oxide, titanium oxide, other color pigments, dyes, etc.); organic solvents (methanol, ethanol, isopropyl alcohol, butanol, acetone, methyl ethyl ketone, ligroin, ethyl acetate, tetrahydrofuran, n-hexane, heptane, isoparaffin-based high boiling point solvents, etc.); adhesion agents (silane coupling agents such as vinyltrimethoxysilane, vinyltriethoxysilane, aminosilane, mercaptosilane, and epoxysilane, epoxy compounds such as glycidyl ether having a polyoxyalkylene skeleton, etc.); vulcanization accelerators (guanidines, aldehyde-amines, aldehyde-ammonias, thiazoles, sulfuric acid, etc.); Phenamides, thioureas, thiurams, dithiocarbamates, xanthates, etc.); vulcanization aids (long-chain fatty acids with 12 or more carbon atoms, such as stearic acid, oleic acid, and palmitic acid, metal oxides such as zinc oxide, magnesium oxide, and lead oxide); anti-aging agents (hindered phenols, mercaptans, sulfides, dithiocarboxylates, thioureas, thiophosphates, thioaldehydes, etc.); UV absorbers and light stabilizers (benzotriazoles, hindered amines, etc.); thixotropic agents (colloidal silica, organic bentonite, fatty acid amides, hydrogenated castor oil, etc.); resins and polymer components other than those mentioned above (thermosetting resins, thermoplastic resins, etc.). These may be used alone or in combination of two or more.
[0061] The hot melt adhesive compositions of the present disclosure may be solvent-free and may not contain any solvent.
[0062] The hot melt adhesive compositions of the present disclosure may be non-reactive and may not contain reactive additives.
[0063] [composition] The amount of crystalline polyolefin (A) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, more preferably 15% by weight or more. The amount of crystalline polyolefin (A) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, preferably 30% by weight or less.
[0064] The amount of amorphous polyolefin (B) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, more preferably 15% by weight or more. The amount of amorphous polyolefin (B) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, preferably 30% by weight or less.
[0065] The amount of the polypropylene wax (C) in the hot melt adhesive composition may be 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more, preferably 20% by weight or more, more preferably 30% by weight or more. The amount of the polypropylene wax (C) in the hot melt adhesive composition may be 75% by weight or less, 70% by weight or less, 65% by weight or less, 60% by weight or less, 55% by weight or less, 50% by weight or less, or 45% by weight or less, preferably 65% by weight or less, more preferably 50% by weight or less.
[0066] The amount of tackifier (D) in the hot melt adhesive composition may be 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% by weight or more, 15% by weight or more, 17.5% by weight or more, 20% by weight or more, 22.5% by weight or more, or 25% by weight or more, preferably 10% by weight or more, more preferably 15% by weight or more. The amount of tackifier (D) in the hot melt adhesive composition may be 40% by weight or less, 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, or 15% by weight or less, preferably 30% by weight or less.
[0067] The amount of the antioxidant (E) in the hot melt adhesive composition may be 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.75% by weight or more, or 1% by weight or more, preferably 0.1% by weight or more. The amount of the antioxidant (E) in the hot melt adhesive composition may be 5% by weight or less, 4% by weight or less, 3% by weight or less, 2% by weight or less, or 1% by weight or less, preferably 3% by weight or less.
[0068] The amount of inorganic filler (F) in the hot melt adhesive composition may be 1% by weight or more, 2.5% by weight or more, 5% by weight or more, 7.5% by weight or more, 10% by weight or more, 12.5% by weight or more, or 15% by weight or more, preferably 2.5% by weight or more, more preferably 5% by weight or more. The amount of inorganic filler (F) in the hot melt adhesive composition may be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, or 5% by weight or less.
[0069] The amount of elastomer (G) in the hot melt adhesive composition may be 0.5% by weight or more, 1% by weight or more, 2% by weight or more, 3% by weight or more, 4% by weight or more, 5% by weight or more, 6% by weight or more, 7% by weight or more, 8% by weight or more, 9% by weight or more, or 10% by weight or more, preferably 1% by weight or more, more preferably 3% by weight or more. The amount of elastomer (G) in the hot melt adhesive composition may be 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7.5% by weight or less, 5% by weight or less, or 2.5% by weight or less, preferably 15% by weight or less, more preferably 10% by weight or less.
[0070] The amount of the other components (I) in the hot melt adhesive composition of the present disclosure may be appropriately selected according to each component. The total amount of the other components (I) in the hot melt adhesive composition may be 0.1% by weight or more, 0.2% by weight or more, 0.5% by weight or more, 1% by weight or more, 2.5% by weight or more, or 5% by weight or more. The total amount of the other components (I) in the hot melt adhesive composition may be 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, 7.5% by weight or less, 5% by weight or less, 2.5% by weight or less, or 1% by weight or less, preferably 20% by weight or less, more preferably 10% by weight or less. The amount of each of the other components (I) in the hot melt adhesive composition may be 0.01% by weight or more, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, 0.75% by weight or more, 1% by weight or more, or 2.5% by weight or more. The amount of each of the other components (I) in the hot melt adhesive composition may be 10% by weight or less, 7.5% by weight or less, 5% by weight or less, 2.5% by weight or less, or 1% by weight or less. The amount of the plasticizer (H) may be based on the amount of the other components (I).
[0071] The total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B) in the hot melt adhesive composition may be 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, 30% by weight or more, 35% by weight or more, 40% by weight or more, 45% by weight or more, or 50% by weight or more, preferably 20% by weight or more, more preferably 30% by weight or more. The total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B) in the hot melt adhesive composition may be 80% by weight or less, 70% by weight or less, 60% by weight or less, 50% by weight or less, 40% by weight or less, or 30% by weight or less, preferably 60% by weight or less. It is preferable that the amount is within the above range from the viewpoint of achieving the effects of the present disclosure.
[0072] The amount of crystalline polyolefin (A) may be 15 parts by weight or more, 25 parts by weight or more, more than 50 parts by weight, 75 parts by weight or more, 100 parts by weight or more, 125 parts by weight or more, 150 parts by weight or more, preferably 25 parts by weight or more, more preferably 60 parts by weight or more, and even more preferably 75 parts by weight or more, relative to 100 parts by weight of amorphous polyolefin (B). The amount of crystalline polyolefin (A) may be 500 parts by weight or less, 450 parts by weight or less, 400 parts by weight or less, 350 parts by weight or less, 300 parts by weight or less, 200 parts by weight or less, 150 parts by weight or less, 100 parts by weight or less, 75 parts by weight or less, or 50 parts by weight or less, preferably 400 parts by weight or less, more preferably 300 parts by weight or less, and even more preferably 200 parts by weight or less, relative to 100 parts by weight of amorphous polyolefin (B). It is preferable that the amount is within the above range from the viewpoint of exhibiting the effects of the present disclosure well.
[0073] The amount of the polypropylene wax (C) may be more than 50 parts by weight, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 100 parts by weight or more, 110 parts by weight or more, or 120 parts by weight or more, preferably 60 parts by weight or more, more preferably 80 parts by weight or more, and even more preferably 90 parts by weight or more, relative to 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). The amount of the polypropylene wax (C) may be 350 parts by weight or less, 300 parts by weight or less, 250 parts by weight or less, 200 parts by weight or less, 150 parts by weight or less, or 100 parts by weight or less, preferably 300 parts by weight or less, more preferably 250 parts by weight or less, and even more preferably 200 parts by weight or less, relative to 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). It is preferable that the amount is within the above range from the viewpoint of exhibiting the effects of the present disclosure well. By making the content equal to or higher than the lower limit, the crystallization promoting effect is improved and mold releasability can be improved, whereas by making the content equal to or lower than the upper limit, adhesion can be improved.
[0074] The amount of the tackifier (D) may be 10 parts by weight or more, 20 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, or 60 parts by weight or more, preferably 20 parts by weight or more, more preferably 40 parts by weight or more, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). The amount of the tackifier (D) may be 150 parts by weight or less, 125 parts by weight or less, 100 parts by weight or less, 75 parts by weight or less, 50 parts by weight or less, or 30 parts by weight or less, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B), preferably 100 parts by weight or less, more preferably 75 parts by weight or less. The amount in the above range is suitable from the viewpoint of exhibiting the effects of the present disclosure well.
[0075] The amount of the inorganic filler (F) may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more, preferably 10 parts by weight or more, more preferably 20 parts by weight or more, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). The amount of the inorganic filler (F) may be 75 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, or 20 parts by weight or less, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B), preferably 60 parts by weight or less, more preferably 40 parts by weight or less. It is preferable that the amount is within the above range in terms of exhibiting the effects of the present disclosure well.
[0076] The amount of the elastomer (G) may be 0.5 parts by weight or more, 1 part by weight or more, 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 10 parts by weight or more, 12 parts by weight or more, or 15 parts by weight or more, preferably 3 parts by weight or more, more preferably 10 parts by weight or more, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). The amount of the elastomer (G) may be 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, or 10 parts by weight or less, preferably 40 parts by weight or less, more preferably 20 parts by weight or less, based on 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B). It is preferable that the amount is within the above range in terms of exhibiting the effects of the present disclosure well.
[0077] [Physical Properties] The hot melt adhesive composition of the present disclosure may have a melt viscosity at 180°C, which is a typical application temperature for hot melt adhesives, of 5,000 mPa·s or more, 7,500 mPa·s or more, 10,000 mPa·s or more, 12,000 mPa·s or more, 15,000 mPa·s or more, 20,000 mPa·s or more, or 25,000 mPa·s or more, preferably 10,000 mPa·s or more, and more preferably 15,000 mPa·s or more. The hot melt adhesive composition of the present disclosure may have a melt viscosity of 200,000 mPa·s or less, 150,000 mPa·s or less, 100,000 mPa·s or less, 50,000 mPa·s or less, 30,000 mPa·s or less, or 20,000 mPa·s or less at 180°C, which is a typical coating temperature for hot melt adhesives, and is preferably 150,000 mPa·s or less, and more preferably 100,000 mPa·s or less. If the melt viscosity is within the above range, it is preferable because no dripping or uneven coating occurs when applied to an adherend. The above melt viscosity is measured using a parallel plate type rheometer at a shear rate of 4.3 sec -1 The values were measured under the following conditions.
[0078] In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when it is rapidly cooled from 160°C at 33°C per minute, the storage modulus at 60°C is 1 x 10 4 Pa or higher, 5×10 4 Pa or more, 1×10 5 Pa or higher, 5×10 5 Pa or more, 1×10 6 Pa or more, 2×10 6 Pa or more, or 3×10 6 Pa or more, preferably 1×10 5 Pa or more, preferably 1×10 6 In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when it is rapidly cooled from 160° C. at a rate of 33° C. per minute, the storage modulus at 60° C. is 1×10 8 Pa or less, 5×10 7 Pa or less, 1×10 7 Pa or less, 5×10 6 Pa or less, 3×10 6 Pa or less, or 1×106 The storage modulus may be measured using a parallel plate rheometer at a shear rate of 4.3 sec -1 The values were measured under the following conditions.
[0079] In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when quenched from 160 ° C. at 33 ° C. per minute, the temperature at which tan δ becomes 1 or less may be 30 ° C. or more, 40 ° C. or more, 50 ° C. or more, 60 ° C. or more, or 70 ° C. or more, preferably 40 ° C. or more, more preferably 60 ° C. or more. In the viscoelastic behavior of the hot melt adhesive composition of the present disclosure when quenched from 60 ° C. at 33 ° C. per minute, the temperature at which tan δ becomes 1 or less may be 100 ° C. or less, 90 ° C. or less, 80 ° C. or less, or 70 ° C. or less, preferably 80 ° C. or less. In addition, tan δ is the loss tangent, and is the ratio of the storage shear modulus (G') to the loss shear modulus (G"), G" / G'. Tan δ was measured using a parallel plate type rheometer at a shear rate of 4.3 sec -1 The values were measured under the following conditions.
[0080] <Method for producing hot melt adhesive composition> The hot melt adhesive composition of the present disclosure can be produced by mixing (A) to (C). For example, the hot melt adhesive composition can be produced by mixing (A) to (C) together with other components as necessary using a heated mixer.
[0081] <Adhesive body and its manufacturing method> The adhesive article of the present disclosure has a first substrate and a second substrate adhered to the first substrate via a hot melt adhesive layer formed from a hot melt adhesive composition.
[0082] The method includes a step of applying the disclosed hot melt adhesive composition to one side of a first substrate to form a hot melt adhesive layer, and a step of adhering the first substrate to a second substrate via the hot melt adhesive layer. The method may further include a curing step for crystallizing the hot melt adhesive layer.
[0083] [Base material] The substrates used as the first substrate and the second substrate are not particularly limited, and examples thereof include wood materials; plastic materials such as polyolefins, polyvinyl chloride, polyurethane, polyester, and epoxy resins; foams of the plastic materials; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, and stainless steel; and inorganic materials such as ceramics. The shape of each substrate is also not particularly limited, and may be, for example, a sheet, foil, plate, or molded body. Each substrate may be made of only one type of material, or may be made of two or more types of materials. The material of the surface of the substrate on which the adhesive layer is provided is preferably nonmetallic, more preferably a resin as described above, and even more preferably a polyolefin, particularly polypropylene.
[0084] [Coating process] In the coating step, various hot melt applicators can be used as a method for coating the substrate, and examples of such methods include methods using a spray gun, a comma coater, a die coater, and a roll coater. When coating the substrate, the adhesive is usually heated to a temperature of 140°C to 200°C to melt the adhesive, and the adhesive can be applied in a molten state. After coating on a release film or release paper, the adhesive may be thermally transferred to another substrate for use. After coating, the adhesive layer may be solidified on the substrate by cooling. The precoated substrate (adhesive layer-containing substrate) obtained after the coating step may be directly subjected to the next molding step, or may be stored before being used in the next step.
[0085] [Adhesion process] In the adhesion step, if necessary, the hot melt adhesive layer may be heated and activated to melt again. Means of heat activation include, for example, heating, ultrasonic waves, high frequency waves, and microwaves, but are not particularly limited. Reactivation is preferably performed immediately before pressure bonding between the precoated substrate and the second substrate. Pressure bonding between the precoated substrate and the second substrate is performed before the hot melt adhesive composition layer surface solidifies. There are no particular limitations on the pressure bonding method, and examples of the pressure bonding method include a press pressure bonding method and a vacuum molding method. The second substrate may be heated or not heated. In addition, if the hot melt adhesive composition layer is in a reactivated state, it does not need to be heated during pressure bonding, but it may be heated simultaneously with pressure as necessary.
[0086] The temperature for heat activation is 100 to 200° C., for example, preferably 100 to 180° C., and more preferably 120 to 160° C., in terms of the surface temperature of the hot melt adhesive layer. The pressure during compression bonding for bonding the first substrate and the second substrate may be 0.01 to 0.5 MPa, preferably 0.01 to 0.20 MPa, and more preferably 0.01 to 0.10 MPa. The time for compression bonding may be, for example, 1 to 300 seconds, preferably 1 to 60 seconds, and more preferably 10 to 30 seconds.
[0087] [Mold contact and peeling process] The method for producing an adhesive body of the present disclosure preferably includes a step of contacting a mold with a hot melt adhesive composition. The hot melt adhesive composition of the present disclosure may be in contact with a mold in the application step or adhesion step. For example, the method for producing an adhesive body of the present disclosure can be suitably used in a vacuum molding method including a step of contacting a mold with a hot melt adhesive composition.
[0088] The material of the mold is not limited, but may be metal, ceramic, or the like, and is preferably metal (for example, various alloys such as aluminum, iron, and stainless steel).
[0089] The method for producing an adhesive article according to the present disclosure may further include a step of peeling the hot melt adhesive layer formed from the hot melt adhesive composition from the mold. The hot melt adhesive layer may be peeled from the mold after cooling.
[0090] <Automobile interior materials and their manufacturing methods> [Automotive interior materials] The automotive interior material of the present disclosure includes an automotive interior molded product, and an automotive interior skin material (hereinafter also referred to as "skin material") that is adhered to the automotive interior molded product via a hot melt adhesive layer formed from the hot melt adhesive composition of the present disclosure. The skin material may be a skin material derived from a hot melt adhesive layer-containing skin material (precoated skin material). Examples of the automotive interior material include door trim, instrument panel, ceiling material, rear tray, pillar, etc.
[0091] The material of the molded product for automobile interior is not particularly limited as long as it is used for automobile interior materials, and examples thereof include wood materials such as paper and wood; plastic materials such as polyolefin (polypropylene, polyethylene, ethylene-propylene copolymer, etc.), polyvinyl chloride, polyurethane, polyester, epoxy resin, nylon, polyester, polycarbonate, polyurethane, acrylic, ABS, PCABS, etc.; rubber materials such as natural rubber and synthetic rubber; metal materials such as aluminum, iron, stainless steel, etc.; and inorganic materials such as ceramics. The molded product for automobile interior may be made of only one type of material, or may be made of two or more types. The material of the surface on which the adhesive layer of the molded product for automobile interior is provided is preferably the above-mentioned material for molded product for automobile interior which is nonmetallic, more preferably the above-mentioned material for molded product for automobile interior which is made of resin, and even more preferably polyolefin such as polypropylene.
[0092] The skin material is not particularly limited as long as it is made of a material used in automobile interior materials, and examples thereof include plastic sheets such as polyolefin, soft polyvinyl chloride, and polyurethane; foams of the above plastics; rubber sheets such as natural rubber and synthetic rubber; fabric materials such as woven fabrics and nonwoven fabrics; and metal foils such as aluminum. The skin material may be made of only one layer, or may include two or more layers of the same or different materials. Examples of skin materials including two or more layers include sheet materials in which one or more layers of the above plastic foams are laminated to one or more layers of the above plastic sheets, rubber sheets, fabric materials, metal foils, etc. Examples of such laminated sheet materials include soft polyvinyl chloride with polyolefin foams, olefin-based thermoplastic elastomers with polyolefin foams, and fabrics with polyurethane foams. The material of the surface on which the adhesive layer of the skin material is provided is preferably the above-mentioned skin material which is nonmetallic, more preferably the above-mentioned skin material which is made of resin, and even more preferably polyolefins such as polypropylene.
[0093] [Manufacturing method for automotive interior materials] The manufacturing method of the automobile interior material of the present disclosure may be such that the adhesive body is an automobile interior material, the first substrate is a skin material, and the second substrate is a molded product for automobile interiors, or conversely, the adhesive body is an automobile interior material, the first substrate is a molded product for automobile interiors, and the second substrate is a skin material.
[0094] An example of a method for producing an automobile interior material may include a step of applying the hot melt adhesive composition of the present disclosure to the back surface of a skin material (for example, the foam layer surface of the skin material) to obtain a skin material containing a hot melt adhesive layer (precoated skin material); a step of reactivating the obtained precoated skin material with a far-infrared heater or the like to melt the hot melt adhesive layer, and then pressing the skin material and the molded article for automobile interior use through the hot melt adhesive layer. It may also include a curing step for crystallizing the hot melt adhesive layer. Note that, when heat pressing is possible in the step of pressing with the substrate, reactivation with a far-infrared heater or the like may not be necessary. Note that the back surface of the skin material means the surface facing the molded article for automobile interior use when the skin material and the molded article for automobile interior use are bonded to each other. EXAMPLES
[0095] The present disclosure will be described more specifically below with reference to examples and comparative examples, but the present disclosure is not limited thereto in any way.
[0096] <Examples 1 to 13 and Comparative Examples 1 to 5> The components shown below were mixed at 180° C. using a mixer (two-arm kneader SV-1-1 manufactured by Moriyama Seisakusho) in the composition shown in Table 1 below to obtain a hot melt adhesive composition.
[0097] [Table 1]
[0098] [Component A] A-1: Dow Chemical Company's VERSIFY 4200 (melting point 84°C, Shore A hardness 94, propylene-ethylene copolymer) A-2: Dow Chemical Company's VERSIFY3000 (melting point 108°C, Shore A hardness 96, propylene-ethylene copolymer) [Component B] B-1: Evonik VESTOPLAST 792 (softening point 108°C, propylene-ethylene-butene copolymer) B-2: REXTAC RT2585 (softening point 132°C, propylene-ethylene copolymer) [Component C] C-1: Viscol 660-P manufactured by Sanyo Chemical Industries (softening point 145°C, weight average molecular weight 8000, polypropylene wax) C-2: Sanwax 171-P manufactured by Sanyo Chemical Industries (softening point 107°C, weight average molecular weight 9500, polyethylene wax) [Component D] D-1: Arakawa Chemical Alcon P140 (softening point 140℃, hydrogenated petroleum-based) D-2: Arakawa Chemical Alcon P90 (softening point 90°C, hydrogenated petroleum-based) D-3: Yasuhara Chemical YS Resin PN1150 (softening point 115°C, terpene type) D-4: YS Polyster T145 (softening point 145°C, terpene phenol type) manufactured by Yasuhara Chemical Co., Ltd. [Component E] E-1: BASF Irganox 1010 (melting point 110°C, hindered phenol type) E-2: BASF Irgafos 168 (melting point 183°C, phosphorus-based) [Component F] F-1: Calcium carbonate 300 mesh manufactured by Shiraishi Calcium Co., Ltd. [Ingredient G] G-1: Mitsui Chemicals Toughmer PN-2070 (melting point 140°C, Shore A hardness 75, propylene-based elastomer) G-2: ExxonMobil VISTAMAXX 6202 (Vicat softening point 48°C, Shore A hardness 61, propylene-based elastomer)
[0099] The hot melt adhesive compositions obtained in Examples 1 to 13 and Comparative Examples 1 to 4 were used to measure melt viscosity and temperature-lowering viscoelasticity as follows. In addition, adhesion test samples were prepared as follows, and evaluations were performed on mold peelability, initial creep, adhesive strength, and heat resistance creep.
[0100] [Melt Viscosity] The measurements were performed using a parallel plate rheometer at a temperature of 180°C and a shear rate of 4.3 sec-1. The results are shown in Table 1.
[0101] [Temperature at which storage modulus and tan δ become 1 or less when quenched] Using a parallel plate rheometer, the viscoelastic behavior was measured at a shear rate of 4.3sec-1 when the adhesive was rapidly cooled from 160°C at a rate of 33°C per minute. The storage modulus at 60°C was recorded. The temperature at which tan δ was 1 or less was also recorded. The results are shown in Table 1. The temperature at which tan δ was 1 or less can be used as an index of mold releasability. At the beginning of the measurement, the hot melt adhesive is in a molten state, so viscosity dominates over elasticity, and tan δ is 1 or more. However, when the hot melt adhesive is rapidly cooled, it solidifies, and elasticity becomes more dominant than viscosity. The temperature at which tan δ is 1 or less can be considered the temperature at which the hot melt adhesive solidifies.
[0102] [Preparation of Adhesion Test Sample 1] The adhesive was applied to the surface of a skin material (TPO / PPF, total thickness 4 mm) using a roll coater at 180°C so that the adhesive layer was 100g / m2. Next, within one day after applying the adhesive, this skin material was heated with a far-infrared heater to 160°C or higher, and immediately thereafter placed on an aluminum plate (thickness 1 mm) and pressed under conditions of 0.1 MPa for 15 seconds to obtain a laminate (adhesion test sample 1).
[0103] [Mold releasability] Within one minute after obtaining the laminate (adhesion test sample 1), the peel strength (N / 25 mm) at 90° peeling was measured using a push-pull gauge. 〇:10N / 25mm or more ×: Less than 10N / 25mm
[0104] [Preparation of Adhesion Test Sample 2] The above adhesive was applied to the surface of a skin material (TPO / PPF, total thickness 4 mm) using a roll coater at 180° C. so that the adhesive layer was 100 g / m2. Next, within one day after applying the adhesive, this skin material was heated with a far-infrared heater to 160° C. or higher, and immediately thereafter placed on a PP board (thickness 2 mm) and pressed under conditions of 0.1 MPa for 15 seconds to obtain a laminate (adhesion test sample 2).
[0105] [Initial creep] After obtaining the laminate (adhesion test sample 2), a load of 200 g / 25 mm was applied in a 90 degree direction in an atmosphere of 60° C., and the peel length (mm) after 5 minutes was measured. The results are shown in Table 1. BA: Interfacial failure on the substrate side FB: Material failure of the skin CF: Cohesive failure of adhesive The number after the destruction state indicates the percentage of destruction state.
[0106] [Adhesive strength] The laminate (Adhesion test sample 2) was aged at 25°C for 24 hours, and then the peel strength (N / 25mm) was measured at 180° peeling. The PP board was fixed with a jig and the skin material was pulled to peel it off. The peeling speed was measured at 200mm per minute. The results are shown in Table 1.
[0107] [Heat creep resistance] The laminate (adhesion test sample 2) was aged at 25°C for 24 hours, and then a load of 100g or 200g / 25mm was applied in a 90 degree direction in an 80°C atmosphere, and the peel length (mm) was measured after 24 hours. The results are shown in Table 1.
[0108] [result] The samples of Examples 1 to 13 had good mold releasability and adhesive properties. In Comparative Example 1, since no crystalline polyolefin (A) was blended, the mold releasability and heat resistance creep were deteriorated. In Comparative Examples 2 and 3, since the blending amount of polypropylene-based wax was outside the range of the present disclosure, the mold releasability was deteriorated. In Comparative Example 4, since a polyethylene-based wax was used, the mold releasability and heat resistance creep were deteriorated. [Industrial Applicability]
[0109] The hot melt adhesive composition of the present disclosure can be used, for example, as a solvent-free adhesive that does not emit VOCs, and has excellent adhesion and heat resistance to resin substrates, particularly olefin substrates. In addition, since it can be easily peeled off from a mold (for example, when bonded by a vacuum molding method), it can be suitably used as an adhesive for automotive interiors.
Claims
1. (A) a crystalline polyolefin having a Shore A hardness of 80 or more; Amorphous polyolefin (B) and Polypropylene wax (C) Including, A hot melt adhesive composition, wherein the amount of the polypropylene wax (C) is 60 parts by weight or more and 300 parts by weight or less per 100 parts by weight of the total amount of the crystalline polyolefin (A) and the amorphous polyolefin (B).
2. 2. The hot melt adhesive composition according to claim 1, wherein the crystalline polyolefin (A) has a melting point of 80° C. or higher.
3. The hot melt adhesive composition of claim 1, wherein the crystalline polyolefin (A) comprises an ethylene-propylene copolymer.
4. The hot melt adhesive composition according to claim 1, wherein the amorphous polyolefin (B) has a softening point of 100°C or higher.
5. The hot melt adhesive composition according to claim 1, wherein the amorphous polyolefin (B) comprises at least one selected from the group consisting of an ethylene-propylene copolymer and an ethylene-propylene-butene terpolymer.
6. The hot melt adhesive composition according to claim 1, wherein the polypropylene-based wax (C) has a softening point of 130°C or higher.
7. 2. The hot melt adhesive composition of claim 1, comprising a tackifier (D).
8. 8. The hot melt adhesive composition according to claim 7, wherein the tackifier (D) has a softening point of 90°C or higher.
9. The hot melt adhesive composition according to claim 7, wherein the tackifier (D) comprises at least one selected from the group consisting of hydrogenated petroleum resins, terpene resins, and terpene phenol resins.
10. 2. The hot melt adhesive composition of claim 1, further comprising an antioxidant (E).
11. 2. The hot melt adhesive composition of claim 1, further comprising an inorganic filler (F).
12. 2. The hot melt adhesive composition of claim 1, comprising an elastomer (G).
13. 2. The hot melt adhesive composition according to claim 1, having a melt viscosity at 180°C of 15,000 mPa·s or more and 100,000 mPa·s or less.
14. The hot melt adhesive composition according to claim 1, which is for use in automotive interior materials.
15. A precoated skin material for automobile interiors, comprising: a skin material for automobile interiors; and a hot melt adhesive layer formed from the hot melt adhesive composition according to any one of claims 1 to 14 on a back surface of the skin material for automobile interiors.
16. 16. An automobile interior material comprising: an automobile interior molded article; and the precoated skin material for automobile interiors according to claim 15, which is adhered to the automobile molded article via the hot melt adhesive layer.
17. A method for producing an adhesive body, comprising the steps of: The adhesive body has a first substrate and a second substrate adhered to the first substrate via a hot melt adhesive layer formed from the hot melt adhesive composition according to any one of claims 1 to 14; A method for producing an adhesive article, comprising a step of contacting a mold with the hot melt adhesive composition.